Kemampuan Berpikir Reflektif dalam Menyelesaikan Soal PISA-Like Ditinjau dari Disposisi Matematis Siswa SMP - Zaidan Farrosa Mukti; Dian Permatasari (Universitas Islam Ahmad Dahlan (UIAD) Sinjai, 2023)
This study aims to describe how students' reflective thinking skills in solving problems similar to PISA by looking at their mathematical dispositions. This research uses a qualitative approach with a qualitative descriptive research type. The subjects in this study were 34 students of class VIII A at an MTsN in Banjarnegara for the 2021/2022 academic year. Data collection techniques used are tests and non-tests. The instruments in this study were reflective thinking ability test sheets, mathematical disposition questionnaires, and interview guidelines. The data analysis technique of this research uses the data analysis technique of Miles and Huberman. The results of the data analysis show that most students with high mathematical dispositions have high and moderate reflective thinking skills. Students with a high mathematical disposition have been able to fulfill the indicators of the reacting, elaborating, and contemplating phases well, although some are still constrained in the reacting phase. Students with a moderate mathematical disposition have moderate reflective thinking skills because they are still constrained in the reacting phase, but are able to fulfill the indicators in other phases well even though they are not systematic. Some students with low mathematical dispositions have not been able to meet the indicators in the reacting, elaborating, and contemplating phases, so their reflective thinking skills are also low. It was also found that subjects with low mathematical disposition were able to meet the indicators in the reacting, elaborating, and contemplating phases so that they had good reflective thinking skills.